Kurilnost razkrojenega lesa - Krelj, Živa (Les (Ljubljana), 2010)
Wood is one of the most important sources of energy. The industrial energy plants mostly use wood in the form of chips or pellets. Chips are often stored outdoors. They are exposed to the fungal decay in such conditions. However, there are no data on the caloric value of decayed wood. Experimental data showed that the brown rot fungus Gloeophyllum trabeum did not affect the calorific value of spruce wood.On the other hand, white rot fungus Trametes versicolor, decreased the calorific value of decayed beechwood by approximately 2,5%.
Keywords: les; kurilnost; kalorična vrednost; razkroj lesa; glive